War in eleventh-century Byzantium
1 online resource (xv, 350 pages)
Keywords: "War in Eleventh-Century Byzantium presents new insights and critical approaches to warfare between the Byzantine Empire and its neighbours during the eleventh century. Modern historians have identified the eleventh century as a landmark era in Byzantine history. This was a period of invasions, political tumult, financial crisis and social disruption, but it was also a time of cultural and intellectual innovation and achievement. Despite this, the subject of warfare during this period remains underexplored. Addressing an important gap in the historiography of Byzantium, the volume argues that the eleventh century was a period of important geo-political change, when the Byzantine Empire was attacked on all sides, and its frontiers were breached. This book is valuable reading for scholars and students interested in Byzantium history and military history"--